2016
DOI: 10.1007/s10661-016-5524-8
|View full text |Cite
|
Sign up to set email alerts
|

Quest to identify geochemical risk factors associated with chronic kidney disease of unknown etiology (CKDu) in an endemic region of Sri Lanka—a multimedia laboratory analysis of biological, food, and environmental samples

Abstract: The emergence of a new form of chronic kidney disease of unknown etiology (CKDu) in Sri Lanka's North Central Province (NCP) has become a catastrophic health crisis. CKDu is characterized as slowly progressing, irreversible, and asymptomatic until late stages and, importantly, not attributed to diabetes, hypertension, or other known risk factors. It is postulated that the etiology of CKDu is multifactorial, involving genetic predisposition, nutritional and dehydration status, exposure to one or more environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 59 publications
4
43
2
1
Order By: Relevance
“…The role of chronic exposure to cadmium (Cd) and arsenic (As) through environmental contamination of agrochemicals remains a highly debated topic among scientists [6,[11][12]. The evidence regarding exposure to heavy metals as measured by levels of urinary excretion in patients and in controls and environmental samples is inconsistent [6,[11][12][13].Novel urinary biomarkers and their association with urinary heavy metals in chronic kidney disease of unknown aetiology in Sri Lank: a pilot study …”
mentioning
confidence: 99%
“…The role of chronic exposure to cadmium (Cd) and arsenic (As) through environmental contamination of agrochemicals remains a highly debated topic among scientists [6,[11][12]. The evidence regarding exposure to heavy metals as measured by levels of urinary excretion in patients and in controls and environmental samples is inconsistent [6,[11][12][13].Novel urinary biomarkers and their association with urinary heavy metals in chronic kidney disease of unknown aetiology in Sri Lank: a pilot study …”
mentioning
confidence: 99%
“…At a more typical human intake of 3 l/day, the corresponding fluoride concentrations would be 0.45 mg/l instead of 1.5 mg/l, and 0.9 µg/l of cadmium instead of 3µg/l. The data of Levine et al (2016) for the composition of water in dug wells give a maximum of 0.168 µg/l of Cd, and 2.05 mg/l of fluoride (but no standard deviations are given), indicating the daily intakes one may expect. If we use a linear model and scale the observed toxicities (in terms of weight loss per mouse) to an intake of about 1/3 the amount of water, then the weight changes for rows 2-6 of table 1 become roughly -1, -2.6, -1.3, -1.6, and -1 g/mouse, still showing significant toxicities above the likely noise threshold of the experiment.…”
Section: Relevance Of the Results To Human Nephrotoxicitymentioning
confidence: 96%
“…However, the concentrations of heavy-metal toxins or pesticides found in the water or soil in the affected area were negligible or inconclusive (Jayatilake , 2013, Nanayakkara et al, 2014 in comparison to the maximum allowed levels (MALs) stipulated by WHO and other regulatory bodies. In contrast, urine samples and biopsies (Jayatilake , 2013, Dahanayake et al, 2012, Levine et al, 2016 of patients showed levels of Cd, As, and Pb well above the expected amounts. Given that most patients were in a relatively advanced state of the disease when diagnosed, these high levels merely indicated the bio-accumulation of toxins which occurs when kidneys become impaired.…”
Section: Introductionmentioning
confidence: 90%
“…A 90-day irrigated rice crop in the rice-growing north-central province of Sri Lanka takes up about 500 mm water [52], i.e., 5 × 10 6 litres of water per hectare as an upper bound. Typical values of Cd concentrations are 0.24 µg/L in canal water [33], or 0.11 µ g of Cd per kg of soil as reported by [39]. Hence we may take a range of values from 0.5 g -1.2 g of Cd uptake by paddy per hectare per season.…”
Section: A Model Based On Water Intakementioning
confidence: 97%